The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1148/radiol.2017170226
|View full text |Cite
|
Sign up to set email alerts
|

Psychoradiologic Utility of MR Imaging for Diagnosis of Attention Deficit Hyperactivity Disorder: A Radiomics Analysis

Abstract: Purpose To identify cerebral radiomic features related to diagnosis and subtyping of attention deficit hyperactivity disorder (ADHD) and to build and evaluate classification models for ADHD diagnosis and subtyping on the basis of the identified features. Materials and Methods A consecutive cohort of 83 age- and sex-matched children with newly diagnosed and never-treated ADHD (mean age 10.83 years ± 2.30; range, 7-14 years; 71 boys, 40 with ADHD-inattentive [ADHD-I] and 43 with ADHD-combined [ADHD-C, or inatten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
136
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 49 publications
2
136
0
1
Order By: Relevance
“…Present study particularly adds to psychoradiology, an evolving specialty as opposed to neuroradiology, mainly for psychiatric and psychological brain (Lui et al, 2016;Kressel et al, 2017;Sun et al, 2018;Port, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…Present study particularly adds to psychoradiology, an evolving specialty as opposed to neuroradiology, mainly for psychiatric and psychological brain (Lui et al, 2016;Kressel et al, 2017;Sun et al, 2018;Port, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…Prior ADHD neuroimaging studies have shown that the inhibitory behavioral control impairments in ADHD are related to regional abnormalities in the inferior frontal gyrus (IFG), anterior cingulate cortex (ACC), temporal/parietal areas, and basal ganglia (Chen et al, ; Chen et al, ; Lei et al, ; Lei, Du, et al, ; Lei, Li, et al, ; Li, He, et al, ; Li, Li, et al, ; Sun et al, ). Using a seed‐based functional connectivity analysis, we found that alterations in frontostriatal circuitry correlated with the degree of inhibitory executive dysfunction in ADHD (Li, He, et al, ; Li, Li, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior ADHD neuroimaging studies have shown that the inhibitory behavioral control impairments in ADHD are related to regional abnormalities in the inferior frontal gyrus (IFG), anterior cingulate cortex (ACC), temporal/parietal areas, and basal ganglia Chen et al, 2016;Lei et al, 2014;Lei, Du, et al, 2015;Lei, Li, et al, 2015;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With advances in quantitative neuroimaging techniques, radiomics may provide a promising modality for predicting WMH progression . Functional MRI has revealed that the destruction of microstructure integrity in cerebral white matter occurs prior to the conventional neuroimaging visibility of WMH, suggesting the existence of a white matter penumbra in which the parenchyma is visually normal but the microstructure has been damaged .…”
mentioning
confidence: 99%
“…12 With advances in quantitative neuroimaging techniques, [13][14][15] radiomics may provide a promising modality for predicting WMH progression. [16][17][18] Functional MRI has revealed that the destruction of microstructure integrity in cerebral white matter occurs prior to the conventional neuroimaging visibility of WMH, suggesting the existence of a white matter penumbra in which the parenchyma is visually normal but the microstructure has been damaged. 12,19 In our previous cross-sectional study, 20 the WMH penumbra could be discriminated by a radiomics textural analysis, indicating that radiomics is a feasible technique to analyze microstructural changes in WMH.…”
mentioning
confidence: 99%